(untitled) (Swiss Medical Weekly, 2015)
QUESTIONS UNDER STUDY: The differentiation between infectious and noninfectious pulmonary complications is challenging. Rapid, accurate microbiological results may allow appropriate antibiotic therapy, withholding or adapting antibiotics, and thus reducing costs and risks of empirical antibiotic therapy. The objective of this proof-of-concept pilot study was to investigate the diagnostic yield of a new polymerase chain-reaction (PCR) and microarray-based rapid molecular diagnostic assay and compare the results to conventional microbiology cultures and clinical judgment. METHODS: Bronchoalveolar lavage specimens were obtained from 35 patients undergoing bronchoscopy for diagnostic reasons. Cases (n = 22) consisted of patients with suspicion of pulmonary bacterial infection. Controls (n = 13) were identified among patients undergoing bronchoscopy for indications other than suspicion of infection. RESULTS: Demographics were similar in cases and controls. The majority (73%) of patients with pulmonary infection were on empirical antibiotic therapy. Among the 22 cases, bacteria were identified by means of PCR in 77% (n = 17) as compared with 41% (n = 9) by culture (p = 0.030). In contrast, controls yielded a PCR positive result in 45% (n = 7), as compared with no positive cultures (p = 0.005). Compared with culture results, PCR had a sensitivity of 87.5% (95% confidence interval [CI] 47.4–97.9) and specificity of 28.6% (95% CI 8.6–58.1) to diagnose bacterial infection. Compared with clinical judgment, corresponding figures were 77.3% (95% CI 54.5–91.1) and 46.2% (95% CI 19.3–74.8), respectively. CONCLUSION: The PCR- and microarray-based rapid molecular diagnostic assay offers an alternative to conventional cultures for detection of potentially pathogenic bacteria in bronchoalveolar lavage of patients with pneumonia. However, the clinical relevance is unclear as it may also detect colonisers in patients without a corresponding infection.